Sealing ability of grar MTA AngelusTM, CPM TM and MBPc used as apical plugs - Fernando Accorsi Orosco; Clovis Monteiro Bramante; Roberto Brandão Garcia; Norberti Bernadineli; Ivaldo Gomes de Moraes (University of São Paulo, 2008)
This study evaluated the sealing ability of apical plugs fabricated with gray MTA AngelusTM sealer, CPM TM sealer and MBPc sealer. The root canals of 98 extracted single-rooted human teeth were instrumented with #5 to #1 Gates Glidden drills according to the crown-down technique until the #1 drill could pass through the apical foramen. The specimens were then prepared with K-files, starting with an ISO 50 until an ISO 90 could be visualized 1 mm beyond the apex. After root canal preparation, the external surface of each root was rendered impermeable and roots were assigned to 3 experimental groups (n = 30), which received a 5-mm thick apical plug of gray MTA AngelusTM, CPM TM and MBPc, and two control groups (n=4). The remaining portion of the canal in the experimental groups was filled by the lateral condensation technique. The teeth of each group, properly identified, were fixed on utility wax by their crowns and were placed in plastic flasks, leaving the apex free and facing upward. The flasks were filled with 0.2% Rhodamine B solution, pH 7.0, so as to completely cover the root apex of all teeth. The sealing ability was analyzed by measuring 0.2% Rhodamine B leakage after all groups had been maintained in this solution for 48 hours. Data were analyzed statistically by Kruskal-Wallis test and Dunn test with a=5%. The results showed that, among the tested materials used for fabrication of apical plugs, MBPc sealer had the least amount of leakage with statistically significant difference (p<0.05).